PESANTREN DAN ISU RADIKALISME (Studi Tentang Asal-Usul Pesantren, pendidikan dan pemikirannya serta Isu Radikalisme Pesantren) - Ruswanto, Ruswanto (Lentera: Jurnal Ilmiah Kependidikan, 2014)
Boarding School is the oldest Islamic institution in Indonesia which has a very important role in the dissemination and strengthening adherence to the Islamic community. But since when actually boarding school began to stand up, not known for certain, but researchers have found that in the 16th century boarding school institutions has grown. Among the researchers also differences of opinion about the origin of the term cottage and boarding school, some argue comes from within and some were of the opinion from the outside. Shelters, boarding school was originally taught about fiqh, tafsir, tasawwuf and classic books as characteristic of traditional boarding school, then along with the emergence of schools of renewal as the effect of advances in science and technology, it also affected the schools boarding school renewal, and this is a positive development Boarding School for it self. However, despite the affected schools boarding school renewal, boarding school never taught schools of radicalism / extremism, because the true ideology contrary to the teachings of Islam and Islamic proselytizing ways.